2010
DOI: 10.1097/acm.0b013e3181f52bed
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Team-Based Learning on Medical Studentsʼ Academic Performance

Abstract: Medical students' higher performance on examination questions related to course content learned through TBL suggests that TBL enhances mastery of course content. Students in the lowest academic quartile may benefit more than highest-quartile students from the TBL strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
301
4
15

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(347 citation statements)
references
References 13 publications
27
301
4
15
Order By: Relevance
“…Some students noted in course evaluations that smaller group recitations may have been helpful when dealing with mathematical problems. Overall, the performance enhancement is consistent with that in a study by Koles and colleagues 14 who found that students involved in TBL demonstrated a greater extent of content mastery than did other instructional approaches. Within the preparatory quizzes, the individual quiz score averaged above 80%, indicating that students were able to read and acquire foundational information on their own.…”
Section: Discussionsupporting
confidence: 80%
“…Some students noted in course evaluations that smaller group recitations may have been helpful when dealing with mathematical problems. Overall, the performance enhancement is consistent with that in a study by Koles and colleagues 14 who found that students involved in TBL demonstrated a greater extent of content mastery than did other instructional approaches. Within the preparatory quizzes, the individual quiz score averaged above 80%, indicating that students were able to read and acquire foundational information on their own.…”
Section: Discussionsupporting
confidence: 80%
“…7,10,13,14 Lower-performing students benefited more from TBL, or had observed no differences in performance between case-based learning and TBL. 22, 25 The proportion of D and F grades was low in both iterations of this course, though a higher proportion of D grades occurred in the first year of TBL. Perhaps these students struggled more in adapting to TBL.…”
Section: Discussionmentioning
confidence: 87%
“…[18][19][20][21][22][23][24][25][26][27][28] Reports of TBL in pharmacy education often use student and faculty perception or performance to examine the initial implementation of TBL. However, no reports have used nationally standardized faculty evaluations of teaching using TBL, examined experiences over a longitudinal implementation of TBL, or reported course outcomes in a pharmacotherapeutics course series that used TBL.…”
Section: Introductionmentioning
confidence: 99%
“…Teaching physicians in many institutions are developing interactive forms of learning, with some using entirely problem-based learning formats and others adapting traditional lectures into team-based learning or case-based presentations. 6,7 Stanford University has been a leader in this field for years and, in partnership with Khan Academy, has developed a program called Stanford Medicine Interactive Learning Initiatives, where medical school faculty can access specialized support to re-design courses and integrate interactive learning. 8 These largescale initiatives are transforming the way students learn and how faculty members teach.…”
Section: Alice Wellington Rollinsmentioning
confidence: 99%